2019
DOI: 10.1111/jph.12806
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity ofColletotrichum gloeosporioidesspecies complex associated withCitruswither‐tip of twigs in Tunisia using microsatellite markers

Abstract: Anthracnose Citrus disease has been associated with several symptoms worldwide and it is recently compromising Citrus production in the Mediterranean area. Four species complexes are mainly involved: Colletotrichum boninense, C. acutatum, C. gloeosporioides and C. truncatum. In this study, we investigated the genetic diversity of Colletotrichum spp. in Tunisia associated with wither‐tip of twigs on Citrus. Specific primers ITS4‐CgInt allowed the identification of C. gloeosporioides species complex in all the 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…Based on morphological characteristics and molecular techniques, 71 isolates (accounting for 83.5% of the total Colletotrichum isolates obtained in this study) were identified as C. siamense, confirming that C. siamense is the dominant species causing anthracnose of rubber tree, coffee, and areca palm in Hainan. The present results also suggest that genetic differentiation among C. siamense isolates from different hosts is small, consistent with the fact that C. gloeosporioides populations in Ethiopia (Moges et al, 2016) and Tunisia (Bahri et al, 2019) are characterized by low genetic differentiation. This may be explained by several factors.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Based on morphological characteristics and molecular techniques, 71 isolates (accounting for 83.5% of the total Colletotrichum isolates obtained in this study) were identified as C. siamense, confirming that C. siamense is the dominant species causing anthracnose of rubber tree, coffee, and areca palm in Hainan. The present results also suggest that genetic differentiation among C. siamense isolates from different hosts is small, consistent with the fact that C. gloeosporioides populations in Ethiopia (Moges et al, 2016) and Tunisia (Bahri et al, 2019) are characterized by low genetic differentiation. This may be explained by several factors.…”
Section: Discussionsupporting
confidence: 90%
“…siamense isolates from different hosts is small, consistent with the fact that C . gloeosporioides populations in Ethiopia (Moges et al, 2016) and Tunisia (Bahri et al, 2019) are characterized by low genetic differentiation. This may be explained by several factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can host among 470 different plants as a pathogen or an endophyte [49]. Most research of CGSC has focused on economic crops [50] or fruits [42]. In this study, we obtained 165 strains belonging to CGSC from three isolation sources (invasive plant A. adenophora healthy leaves and symptomatic leaves, and neighbor plants symptomatic leaves) in 11 geographic sites (belonging to four invasion ages of A. adenophora).…”
Section: Discussionmentioning
confidence: 99%
“…CGSC may be simpler to consider as a species complex rather than using intraspeci c designations for practical reasons [39,40]. Moreover, because genetic diversity in a species is generally limited, researches on population genetic diversity have been conducted on a species complex, such as CGSC [23,41,42]. In this study, therefore, all DNA sequences that were identi ed as the CGSC were included in subsequent genetic analyses.…”
Section: Dna Extraction Pcr Ampli Cation and Sequencingmentioning
confidence: 99%